2016
DOI: 10.1186/s13643-016-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early postnatal discharge from hospital for women and infants: a systematic review protocol

Abstract: BackgroundThe length of postnatal hospital stay has declined over the last 40 years. There is little evidence to support a policy of early discharge following birth, and there is some concern about whether early discharge of mothers and babies is safe. The Cochrane review on the effects of early discharge from hospital only included randomised controlled trials (RCTs) which are problematic in this area, and a systematic review including other study designs is required. The aim of this broader systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…There is a lack of robust evidence for current postpartum practice on newborn LOS, particularly for safe discharge of babies born early term (37–38 weeks’ gestation) or late preterm (34–36 weeks’ gestation), who are at particularly high risk of early readmission for jaundice or feeding problems . We therefore explored four approaches for modelling the association between newborn LOS and risk of readmission, and assessed the impact of unmeasured confounding by clinical condition after birth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of robust evidence for current postpartum practice on newborn LOS, particularly for safe discharge of babies born early term (37–38 weeks’ gestation) or late preterm (34–36 weeks’ gestation), who are at particularly high risk of early readmission for jaundice or feeding problems . We therefore explored four approaches for modelling the association between newborn LOS and risk of readmission, and assessed the impact of unmeasured confounding by clinical condition after birth.…”
mentioning
confidence: 99%
“…2 Evidence on safe early discharge is conflicting. [3][4][5] Much of the evidence comes from the United States, where rates of neonatal readmissions declined following legislation in 1996 mandating insurance for a minimum 48-h hospital stay for normal deliveries. [6][7][8] However, several observational studies have demonstrated that decreasing the length of postpartum stay does not increase readmission rates, given adequate postnatal care outside of hospital.…”
mentioning
confidence: 99%
“…The length of postnatal hospital stay has been suggested as a possible factor contributing to dissatisfaction with postnatal care amongst childbearing women. Globally there has been a decreasing trend in the length of postnatal stay for women in western countries who choose to birth in hospital (Brown, Small, Argus, Davis, & Krastev, ; Jones, Taylor, MacArthur, Pritchett, & Cummins, ). This decreasing length of stay has led to early discharge policies that according to Jones et al.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of mothers in the state of Victoria revealed that only 50% of women rated their postnatal care as 'very good' in comparison to antenatal (67% very good) and intrapartum care (72% very good) (McLachlan et al, 2009) The length of postnatal hospital stay has been suggested as a possible factor contributing to dissatisfaction with postnatal care amongst childbearing women. Globally there has been a decreasing trend in the length of postnatal stay for women in western countries who choose to birth in hospital (Brown, Small, Argus, Davis, & Krastev, 2009;Jones, Taylor, MacArthur, Pritchett, & Cummins, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation